The abdominal cocoon - Yip, F.W.; Lee, S.H. (Wiley, 1992)
Since it was first described in 1978 the abdominal cocoon continues to be a rare cause of intestinal obstruction. So far this rare condition where the small intestine is encased in a fibrous membrane has been reported only in females. Diagnosis is usually made at laparotomy and the treatment of choice is lysis of adhesions. Proper recognition of this benign condition will result in the correct management of it and prevent unnecessary bowel resections. Five new cases including one male patient, together with a review of previous reports in the English literature, are presented.